Microbiological and biochemical quality of patin (pangasius pangasius) fillets under modified atmosphere packaging - Shariat, Maryam (2012)
Fresh fish are very susceptible to spoilage with a short shelf life due to their biological composition. The combined effects of microbiological and chemical changes gradually reduce the quality of fish during storage and are involved in spoilage process. Modified Atmosphere Packaging (MAP) is generally recognized as a useful preservation technique in extending the shelf life of fish and fish products. Consumers’ tendency towards selection of fresh over processed or frozen fish has led MAP to become the most widely used technique in recent years. Thus, the present study was undertaken to determine the effects of vacuum packaging and MAP with different gas mixtures on the shelf life of patin fillets stored in refrigeration temperature. Patin (Pangasius pangasius)is a freshwater catfish which is widely aquacultured in Malaysia. Although patin fish is considered as a popular and high valued species, none has been reported about the modified atmosphere storage of this fish previously. In the present study, after purchasing live patin fish from fish land pond, which was located in Serdang, they were transferred to the laboratory and filleted immediately. Patin fillets were packed under vacuum and four different MAP treatments namely MAP1 (5% O2 + 40% CO2 + 55% N2), MAP2 (5% O2 + 60% CO2 + 35% N2), MAP3 (5% O2 + 80% CO2 + 15% N2) and MAP4 (100% CO2) and subjected to microbial, chemical and sensory analyses at time points of 0, 3, 6, 9, 12, 15, 18 and 21 days during storage at 4ºC. Air stored samples were used as control and the results obtained for all treatments were compared with the control. Microbiological analyses were performed for total mesophilic and psychrotrophic aerobic counts, total mesophilic and psychrotrophic anaerobic counts, proteolytic bacterial counts and Enterobacteriaceae counts. Biochemical analyses were carried out for pH, total volatile bases nitrogen (TVBN) and lipid oxidation (TBA test). Before packaging the fillets, proximate composition and fatty acids profile of the fillets were also determined in fresh fish at day 0. The dominant aerobic mesophilic microflora in the fillets under air storage and MAP4 (100% CO2) were identified at each sampling day. The highest bacterial counts for all the bacterial groups were observed in air storage, followed by vacuum packaging (VP), MAP1, MAP2, MAP3 and MAP4,respectively. Aerobic mesophilic counts for the patin fillets under air storage exceeded the threshold value for microbial spoilage (107cfu/g) after 9 days, whereas those kept under VP, MAP1, MAP2 and MAP3 reached the same value on day 14, 17, 18 and 21, respectively. Patin fillets packaged in MAP4 (100% CO2) did not reach the spoilage value throughout 21 days of storage. Total aerobic mesophilic counts in air stored patin fillets increased approximately 5.5 log cycle throughout storage period, whereas those packaged under 100% CO2 showed around 3 log cycle increase within 21 days. This clearly indicated the powerful effect of carbon dioxide against bacterial growth at the highest concentration. The sensory quality of all patin fillets was acceptable during the first 13 ±1 days of aerobic storage, 16 ±1 days of storage in vacuum packaging and MAP1, 18 ± 1 days of storage in MAP2 and 19 ± 1 days of storage in MAP3. The overall sensory scores for the fillets packed in 100% CO2 (MAP4) was higher than the acceptable limit at the end of storage period (21 days). A good correlation was found between the microbial (TVC) and sensory data (overall acceptability) for all storage conditions (correlation coefficient (r) between -0.943 to -0.987). Microbiological identification showed that Aeromonas species were the dominant bacteria during air storage while lactic acid bacteria (LAB) formed the majority of the isolates from fillets kept under 100% CO2 (MAP4). The proximate and fatty acids composition of patin fillets showed they consisted of 5.71g lipid/100g which was susceptible to oxidation due to the high amount of unsaturated fatty acids (63.86%) versus saturated fatty acids (31.14%). The chemical parameters revealed 100% CO2 (MAP4) and vacuum packed fillets had the lowest TBARS values whereas air-stored fillets showed the highest TBA values. TVBN increased negligibly during storage of patin fillets in all treatments and did not exceed the acceptability limit (35Nmg/100 g). The results of this study indicated that 100% CO2 was found to be the most effective atmosphere for storage of patin fillets at 4ºC since this condition was associated with superior microbiological, biochemical and sensory attributes.